Optimizing the Role of Posyandu Cadres in Providing Nutrition Education and Stimulation as Prevention and Handling of Stunting - Ike Fitrah Atul Chabibah; Dyta Anggraeny; Rodela Agnesia Irot (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The policy direction and action plan for the public health program in the period 2020-2024 includes a target to reduce the stunting rate from 27.7% in 2020 to 14% in 2024. Community health workers, known as cadres, are considered crucial in the implementation of Posyandu activities and are expected to mobilize community participation. Enhancing the capacity of Posyandu cadres is important in terms of their knowledge, understanding, and abilities, and one approach is through cadre empowerment activities. These activities aim to ensure early detection of stunting cases for prompt intervention. The PkM activities were conducted through a training session for six Posyandu cadres assigned to Environment V in Bailang Village, Bunaken Sub-district, Manado City. The training was provided to the cadres during the screening process for stunting cases through the PoT ASHANTI program in Bailang Village. The intervention activities were carried out from March 6th to 8th, 2023. A pre-test was conducted before the intervention, and a post-test was administered after the training. The results of the training indicate an improvement in the knowledge and skills of the Posyandu cadres. The implementation of nutrition education and simulation as preventive and treatment measures for stunting proved to be effective. This is evident from the evaluation of the PkM activities conducted during the Posyandu schedule, where there was an increase in visits from February 2023 (pre-intervention), with 13 visits, to March 2023 (post- intervention), with 18 visits. The provision of nutrition education and stimulation has increased the knowledge and skills of the cadres, which serves as an indicator for the prevention and management of stunting. The cadres now better understand their roles and can assist in early stunting detection in their respective areas.